KEHIDUPAN SOSIAL EKONOMI PEKERJA PEREMPUAN DI PERUSAHAAN TAMBANG PT. WEDA BAY NICKEL (Studi Kasus Masyarakat Lingkar Tambang Desa Lelilef Kecamatan Weda Tengah Kabupaten Halmehara Tengah). - Taslim, Sunaria; Pratiknjo, Maria Heny; Mulianti, Titiek (Universitas Sam Ratulangi, 2020)
The presence of PT Weda Bay Nickel (WBN) Company for The Central Halmahera Site in Tanjung Ulie Lelilef Village, Central Vedic District, has brought hope for the Mining Circle community, especially those in the Ring One category with the hope of absorbing the male and female labor.The opportunity for women to be accepted as mine employees is very welcome in the midst of a business field known to the general public as